Investigation of Mavlana Aznab Sheberghani school students’ reluctance in math subject - Nazari, Muhammad Rafi (International Journal of Innovative Research and Scientific Studies, 2021)
The subject of this study is to investigate causes of students’ disinterest in education department or domain (secondary school of Mavlana Aznab Sheberghani). The essential and important objective of this study is to identify causes of students’ disinterest in math subject. This study was a filed and applied research. The instrument was questionnaire and filled in by students in the field. One of the reasons of students’ disinterest in math subject in secondary school is weaknesses in foundation and mathematical thinking. In math instruction, these are the problems that need to be considered: to have professional teachers, qualified and strong management and leadership based on the system of reward and punishment, use of technology in teaching math subject, and use of appropriate curriculum based on society’s needs. These are the primary needs of our society. The importance of theoretical research is to examine various theories on the title of study (causes of students’ disinterest in math subject) and find out different variables and answer to the research questions appropriately. The importance of research is to find out the causes of lack of progress in learning math subject. The results indicate that there are lots of barriers and problems in math learning among students. It is important to increase students’ interests and motivation by eliminating the problems.